Interlimb relation during the double support phase of gait: An electromyographic, mechanical and energy-based analysis. (March 2013) - Sousa, Andreia SP; Silva, Augusta; Tavares, João Manuel RS
The purpose of this study is to analyse the interlimb relation and the influence of mechanical energy on metabolic energy expenditure during gait. In total, 22 subjects were monitored as to electromyographic activity, ground reaction forces and VO2 consumption (metabolic power) during gait. The results demonstrate a moderate negative correlation between the activity of tibialis anterior, biceps femoris and vastus medialis of the trailing limb during the transition between mid-stance and double support and that of the leading limb during double support for the same muscles, and between these and gastrocnemius medialis and soleus of the trailing limb during double support. Trailing limb soleus during the transition between mid-stance and double support was positively correlated to leading limb tibialis anterior, vastus medialis and biceps femoris during double support. Also, the trailing limb centre of mass mechanical work was strongly influenced by the leading limbs, although only the mechanical power related to forward progression of both limbs was correlated to metabolic power. These findings demonstrate a consistent interlimb relation in terms of electromyographic activity and centre of mass mechanical work, being the relations occurred in the plane of forward progression the more important to gait energy expenditure.